2014
DOI: 10.1124/dmd.114.057794
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolism of Furan in Rodent and Human Cryopreserved Hepatocytes

Abstract: Furan is a liver toxicant and carcinogen in rodents. Although humans are most likely exposed to furan through a variety of sources, the effect of furan exposure on human health is still unknown. In rodents, furan requires metabolism to exert its toxic effects. The initial product of the cytochrome P450 2E1-catalyzed oxidation is a reactive a,b-unsaturated dialdehyde, cis-2-butene-1,4-dial (BDA). BDA is toxic and mutagenic and consequently is considered responsible for the toxic effects of furan. The urinary me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…The acetylated BDA-lysine compound 1 was the most abundant furan metabolite detected in the human samples, consistent with the observation that this direct reaction product was the dominant BDA-derived metabolite of furan in human hepatocytes. 17 The sulfoxide metabolite 3 was the second most abundant BDA-derived reaction product detected in most of the human samples; however, sulfide 2 was more abundant than the sulfoxide 3 in some of the samples. The latter case occurred more frequently in the Asian cohort samples and was not associated with smoking status.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The acetylated BDA-lysine compound 1 was the most abundant furan metabolite detected in the human samples, consistent with the observation that this direct reaction product was the dominant BDA-derived metabolite of furan in human hepatocytes. 17 The sulfoxide metabolite 3 was the second most abundant BDA-derived reaction product detected in most of the human samples; however, sulfide 2 was more abundant than the sulfoxide 3 in some of the samples. The latter case occurred more frequently in the Asian cohort samples and was not associated with smoking status.…”
Section: Discussionmentioning
confidence: 91%
“…The total sum of cysteine-BDA-lysine derived metabolites ( 2 – 5 ) was less than the BDA-lysine metabolite 1 . This finding was somewhat surprising given that studies in rat hepatocytes indicated that the formation of glutathione-BDA-lysine metabolites occurred to a much greater extent than metabolite 1 ; 3,17 glutathione-BDA-lysine is likely a major precursor to metabolites 2 – 5 . 3,17 A likely explanation for this discrepancy is that we are not accounting for all of the cysteine-BDA-lysine-derived metabolites reported in rat urine.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similar cyclic molecules derived from cis-enedial and GSH were previously documented (Chen et al, 1995;Peterson et al, 2005Peterson et al, , 2011Gates et al, 2014). In addition, we performed a separate microsomal incubation in which GSH was replaced with NAC, and no such metabolite formed by the intramolecular cyclization occurring in the GSH-fortified incubation was detected.…”
Section: Discussionmentioning
confidence: 99%